(untitled) (Global Scientific Review, 2024)
This research paper explores the concept of "concept" within the framework of cognitive linguistics, paying particular attention to its relationship with language culture. Drawing on key theories of cognitive linguistics, the paper explores how concepts are formed, structured and expressed through language. It examines the role of cultural factors in the formation of conceptual systems and examines the influence of language culture on the acquisition, expression and communication of concepts. By analyzing empirical studies and theoretical perspectives, this article aims to comprehensively understand the complex interplay between concepts, cognition, and language culture.